2017
DOI: 10.4236/jacen.2017.64013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Health and Environmental Risks of Pesticide Products Used in Market-Gardening in the City of Ngaoundere (Cameroon)

Abstract: The aim of this survey was to identify the active ingredients of phytosanitary products generally used in the market-gardening, to evaluate the behavior of market gardeners, environmental and sanitary risks link to the use of phytosanitary products. Results revealed that 8 actives ingredients are regularly used: paraquat, atrazine, glyphosate, chlorpyrifos-éthyl, cypermethrin, maneb, mancozeb and diuron. The contamination of running water and rivers is caused by the fact that 81.25% of them are washing their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…to insecticides according to seasonal or temporal variations or type of breeding habitats [ 10 , 50 ]. Unsafe storage and disposal of expired pesticides and empty pesticide containers were recorded, showing the need for more awareness among farmers and the community to promote best practices [ 105 , 109 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…to insecticides according to seasonal or temporal variations or type of breeding habitats [ 10 , 50 ]. Unsafe storage and disposal of expired pesticides and empty pesticide containers were recorded, showing the need for more awareness among farmers and the community to promote best practices [ 105 , 109 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Jhalendra et al (2018), this failure could be explained by the very high cost of PPE which consisting of wearing eyes protective goggles, waterproof protective clothing, waterproof gloves, rubber and nitrile boots. However, the results of Assokeng et al (2017) and Sonchieu et al (2019) respectively in Ngaoundere (North Cameroun) and Foumbot (West Cameroun) showed that the wearing of inadequate protective equipment and the consumption of surrounding water represented a danger to the health of market gardeners. Thus, signs and symptoms related to pesticides such as headache, stomach ache, dizziness, skin irritation and breathing difficulties were recorded.…”
Section: Discussionmentioning
confidence: 97%
“…In this basin, soil samples were collected at a depth of 0-20 cm to form pots and their characteristics are presented in Table 1. Soils from the vegetable production basin were used because studies on the dynamics of linuron residues in this soil had shown an accumulation of linuron residues at this depth [16] . For each, three growth phases were chosen according to their growth cycle: vegetative phase, flowering phase and maturation phase.…”
Section: Soil Sampling Areamentioning
confidence: 99%